Characterization of a DNA binding activity in DNAse I hypersensitive site 4 of the human globin locus control region. - Walters, M (1991)
A portion of the beta-globin Locus Control Region (LCR), which included DNAse I hypersensitive site 4 (HS4), was analyzed for its interactions with nuclear extracts and its contribution to LCR activity in a functional assay. In gel retardation assays, a short fragment from HS4 formed complexes with nuclear extracts from both erythroid and nonerythroid cells, and a core protected sequence 5'GACTGGC3' was revealed by DNAse I protection and methylation interference studies. This sequence resembles the binding sites of CCAAT-family members. Purified CP-2 but not CP-1 was shown to bind this HS4 sequence in a gel shift reaction, suggesting that the HS4 binding activity shares some sequence specificity with the CCAAT-factor family. Utilizing a transient expression assay in murine erythroleukemia cells, steady-state RNA levels were measured from pairs of LCR constructs linked to distinguishable beta-globin reporter genes. A short DNA fragment from HS4 which included the binding site for this novel binding activity accounted for most of the contribution to high level expression made by the entire HS4 region.